2021
DOI: 10.1088/2058-6272/abf9fd
|View full text |Cite
|
Sign up to set email alerts
|

Influence of non-uniform electric field distribution on the atmospheric pressure air dielectric barrier discharge

Abstract: The dielectric barrier discharge (DBD) in air at atmospheric pressure is not suitable for industrial applications due to its randomly distributed discharge filaments. In this paper, the influence of the electric field distribution on the uniformity of DBD is theoretically analyzed and experimentally verified. It is found that a certain degree of uneven electric field distributions can control the development of electron avalanches and regulate their transition to streamers in the gap. The discharge phenomena a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…In 2017, Liu et al [97] proposed a line-plane electrode with floating voltage electrode, which was composed of high-voltage electrode, floating voltage electrode, air gap, barrier medium, and metal electrode. The research on the electric field of the line-plane electrode with floating voltage electrode showed that the strong electric field regions that were conducive to the initial discharge were F I G U R E 1 5 DBD experimental device (a) water electrode air DBD [96]; (b) floating voltage electrode DBD [97]; (c) multilayer DBD [98]; and (d) curved plate electrode DBD [99].…”
Section: Air H-dbdmentioning
confidence: 99%
See 4 more Smart Citations
“…In 2017, Liu et al [97] proposed a line-plane electrode with floating voltage electrode, which was composed of high-voltage electrode, floating voltage electrode, air gap, barrier medium, and metal electrode. The research on the electric field of the line-plane electrode with floating voltage electrode showed that the strong electric field regions that were conducive to the initial discharge were F I G U R E 1 5 DBD experimental device (a) water electrode air DBD [96]; (b) floating voltage electrode DBD [97]; (c) multilayer DBD [98]; and (d) curved plate electrode DBD [99].…”
Section: Air H-dbdmentioning
confidence: 99%
“…However, in air, due to the quenching of the nitrogen metastable N 2 (A) by O 2 , Penning ionisation cannot be used for the electron creation to maintain discharge at a low electric field. Consequently, specific electrode structures such as mesh electrodes [68,[87][88][89] and asymmetric electrical structures with small radius components [97,99] were designed to produce seed electrons. Some materials such as electret material [68,[87][88][89][90][91][92][93][94][95][96][97][98][99] and porous alumina ceramic [21,100,101] can also facilitate the seed electron generation in favour of the homogeneous mode.…”
Section: Air H-dbdmentioning
confidence: 99%
See 3 more Smart Citations